FEATURES OF THE CLINICAL COURSE OF BRONCHITIS OF DIFFERENT ETIOLOGIES IN INFANT CHILDREN - Sagdullaeva Mafura Abdukarimovna; Abdukodirov Toshtemir cattaboy coals (Galaxy International Interdisciplinary Research Journal, 2023)
The article presents the features of the clinical course of bronchitis in young children when they are exposed to various etiological factors. In the process of research, the main aspects of the course of bronchitis in children were identified .